The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1093/rheumatology/ket216
|View full text |Cite
|
Sign up to set email alerts
|

The clinical utility of accelerometry in patients with rheumatoid arthritis

Abstract: Patients with RA lead a significantly more sedentary lifestyle than healthy controls and show diurnal differences in physical activity due to morning stiffness and fatigue. Higher levels of habitual physical activity may be protective of functional capacity and are highly associated with improved health-related quality of life in RA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
3
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 21 publications
3
88
3
8
Order By: Relevance
“…However, when controlled for potential explanatory variables, only reduced activity due to fatigue, physical fatigue and disease activity were found to be statistically significantly lower in patients being regularly physically active. Findings from this study support previous studies documenting low levels of physical activity and increased sitting time in patients with RA compared to controls [9,[28][29][30]. Although no direct comparison was made in the present study, we found that 27 % of the patients in our study reported being primarily sedentary compared to 16.4 % of the Danish general population [31].…”
Section: Discussionsupporting
confidence: 88%
“…However, when controlled for potential explanatory variables, only reduced activity due to fatigue, physical fatigue and disease activity were found to be statistically significantly lower in patients being regularly physically active. Findings from this study support previous studies documenting low levels of physical activity and increased sitting time in patients with RA compared to controls [9,[28][29][30]. Although no direct comparison was made in the present study, we found that 27 % of the patients in our study reported being primarily sedentary compared to 16.4 % of the Danish general population [31].…”
Section: Discussionsupporting
confidence: 88%
“…This is in contrast to previous reports in RA that did not characterize or report PA across different intensity categories. (5, 19, 31, 32) The findings confirm that individuals with RA are largely sedentary and spend the majority of their PA in light intensities. Only 17% of participants met the PA guidelines, which is similar to other reports in arthritis, (14, 33, 34) but lower than the reported rate of 44–64% in the general population.…”
Section: Discussionsupporting
confidence: 63%
“…A recent report using accelerometers (Actical) compared physical activity in persons with RA to gender and BMI-matched controls, but the controls were significantly younger than the persons with RA, calling into question the conclusion that persons with RA engage in more sedentary and less total physical activity than healthy people. [15]…”
Section: Discussionmentioning
confidence: 99%